Dialektika Ormas Islam dalam Pendekatan Sosiologi Dakwah, Aktualisasi Dakwah Moderat di Desa Maos Lor Kabupaten Cilacap - Mujamil, Ashari; Fatimah, Siti (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2023)
The purpose of this study is to examine the dialectics of Islamic mass organizations in Maos Lor Village as da'wah institutions that have an impact on the social dynamics of society. A qualitative field study with a sociology of da'wah approach that accommodates the science of da'wah and sociology, this research uses analytical tools in the form of social construction theory and functional structural theory. The results found that in the dialectic that occurs, each mass organization has different goals so that it needs periodic social interaction to adapt and integrate until the achievement of moderate community life. Socio-historically, there is friction in ideology and diversity attitudes that are reflected in differences in da'wah strategies and activities, even the turmoil over mosques for da'wah bases. However, as the development of this attitude leads to moderation which is characterized by the da'wah activities of each mass organization as well as openness and tolerance. From the results of this research, the implications obtained academically are in the form of developing interdisciplinary Islamic studies, as well as socially religious in the form of a reflection of religious moderation at the level of even small communities.